Video game as a preoperative warm-up for laparoscopic surgery - Fernando Korkes; Marcelo Langer Wroclawski; Alessandro Tavares; Oseas de Castro-Neves Neto; Marcos Tobias-Machado; Antonio Carlos Lima Pompeo; Eric Roger Wroclawski (Einstein (São Paulo), 2009)
Objective: The aim of the present study was to assess the influence of video game as warm-up before dry-lab laparoscopic activities. Methods: Eleven medical students participated in this prospective randomized crossover study. Students were divided into two groups. Students in Group 1 had to execute an interrupted suture with the dominant hand using a standardized technique (non-video game group). Students in Group 2 performed the same suture, but after playing a video game match (video game group). After this initial task, groups were crossed. The time spent to complete each task was recorded, and the participants and observers had to judge the performance for each laparoscopic exercise. These variables were used as a measure of performance. Rresults: Mean time for laparoscopic surgery in this subset of inexperienced laparoscopic students was similar between non-video game versus video game groups (254.6 ± 187.7 versus 255.8 ± 183.6; p = 0.875). Subjective impression of observers regarding students’ performance was also similar (p = 0.662), but subjective impression of the participant about his own performance was different between both groups, with 64.7 versus 20.0% of participants that considered their performance good for video game versus non-video game groups (p = 0.044). Cconclusions: In conclusion, video games used as warm-up for laparoscopic practice seem to make inexperienced surgeons more confident and comfortable with the procedures, even though objective measures, as operative time and observers’ impression of surgeons’ performance do not seem to be affected by video game warm-up.